Metabolic routes along digestive system of licorice: multicomponent sequential metabolism method in rat. (17th November 2015) - Zhang, Lei; Zhao, Haiyu; Liu, Yang; Dong, Honghuan; Lv, Beiran; Fang, Min; Zhao, Huihui
Abstract: This study was conducted to establish the multicomponent sequential metabolism (MSM) method based on comparative analysis along the digestive system following oral administration of licorice ( Glycyrrhiza uralensis Fisch., leguminosae), a traditional Chinese medicine widely used for harmonizing other ingredients in a formulae. The licorice water extract (LWE) dissolved in Krebs–Ringer buffer solution (1 g/mL) was used to carry out the experiments and the comparative analysis was performed using HPLC and LC‐MS/MS methods. In vitro incubation, in situ closed‐loop and in vivo blood sampling were used to measure the LWE metabolic profile along the digestive system. The incubation experiment showed that the LWE was basically stable in digestive juice. A comparative analysis presented the metabolic profile of each prototype and its corresponding metabolites then. Liver was the major metabolic organ for LWE, and the metabolism by the intestinal flora and gut wall was also an important part of the process. The MSM method was practical and could be a potential method to describe the metabolic routes of multiple components before absorption into the systemic blood stream. Copyright © 2015 John Wiley & Sons, Ltd.